Tightly coupled governance for loosely coupled wicked problems: the train explosion in Lac-Mégantic case. (2016) - Therrien, Marie-Christine; Valiquette-L'Heureux, Anais; Normandin, Julie-Maude; Smits, Pernelle
Risk management is based on a network of actors, interdependent of each other where the decisions will impact the actions of the others. One danger is then loosely coupled governance where the lack of coordination, overlaps and discontinuities create vulnerabilities leading to crisis situations. The analysis of the train derailment in Lac-Mégantic shows how the complexity of wicked problems led to the crisis. To analyse the complexity and interdependence of actors and issues three narratives are used: network governance, sensemaking and risk regulation regime. Finally, strategies are proposed to reflect on unlocking opportunities for action.